Social history; Morellet; Social anthropology; History of the book (Voltaire Foundation, 2017)
I. Besterman Prize 2005 Myrtille Méricam, Présence de l’Antiquité dans l’œuvre de Voltaire: quelques réflexions sur la figure de Jules César Sean Takats, Science without scientists: modern cooking in the eighteenth century II. Social history David Garrioch, La sécularisation précoce de Paris au dix-huitième siècle Mary Trouille, Buried alive: Genlis’s Gothic tale of marital violence in ‘Histoire de la Duchesse de C***’ III. Morellet Dorothy Medlin, André Morellet and the Trudaines Dorothy Medlin, 'Vive Louis-le-désiré!’: André Morellet et la restauration de la monarchie, 1814-1817 Jeffrey Merrick, Corruption versus honnêteté: Morellet’s assessment of the French political scene in May 1774 IV. Social anthropology Benoît De Baere, La philosophie de l’homme de Buffon et son défi à l’égard de l’‘inhumaine alliance des choses’ V. History of the book Claudine Poulouin, Les paradoxes de la publication des textes de Fontenelle: discrétion, dissimulation, affirmation de soi Frank A. Kafker and Jeff Loveland, The elusive Laurent Durand, a leading publisher of the French Enlightenment Paul Benhamou, Diffusion of forbidden books: four case studies Summaries